The gatecrasher - Wickham, Madeleine, 1969- (New York : Thomas Dunne Books/St. Martins Press, 2007)
Fleur Daxeny gatecrashes funerals in the hopes of picking up rich and vulnerable men, but when she becomes involved with Richard Favour, she discovers that she is in too deep, and that she wants more than his money.
Originally published: London : Black Swan, 1998.
Keywords: Swindlers and swindling -- Fiction; Satire; Black humor (Literature); Humorous fiction